Allergy management in primary care across European countries – actual status. Issue 7 (4th June 2013) - Agache, I.; Ryan, D.; Rodriguez, M. R.; Yusuf, O.; Angier, E.; Jutel, M.
Abstract The standard of care for allergies within a primary care (PC) setting has a strong influence on disease prevention and control, quality of life, and patient satisfaction. The level of knowledge of allergic diseases and the accessibility to regular follow‐up are essential. EAACI and IPCRG conducted a survey to evaluate the actual status of care for allergic diseases in PC. Access to allergy and asthma specialist treatment was identified as the greatest 'unmet need'. The average waiting time between a referral and being seen in a public health service is usually >6 weeks. Referring the patients to an 'organ' specialist is much easier compared with referral to an allergist. Most PCPs have access to blood tests for total and specific IgE. Skin prick testing is available in only half of the cases, while provocation tests, allergen quantification in homes, and a dietician service are even less available. 20.6% of practices do not have access to allergy tests at all. Other issues raised were low political or general public awareness, lack of understanding by the patients of their allergic disease, the need to invest in PC, and to achieve sufficient competence at the appropriate level of care.